The Influence of Learning Leadership, Educational Management Knowledge, Work Motivation and Job Satisfaction on the Organizational Commitment - Jalaluddin, Jalaluddin; Khafidah, Wahyu; Usman, Musliadi Bin; Hammoodi, Samira (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the influence of instructional leadership, knowledge of educational management, work motivation, and job satisfaction on the organizational commitment of school principals. Using a quantitative approach and survey method, this study systematically measures the influence of independent variables on organizational commitment. The technique used in sampling is proportional random sampling. Data analysis involves validity and reliability tests, confirmatory factor analysis (CFA), and Structural Equation Modeling (SEM) to assess direct and mediation effects. The results show that educational management significantly affects organizational commitment, but this effect is negatively mediated by job satisfaction and work motivation. Although good management can increase motivation and job satisfaction, it does not continually strengthen organizational commitment. Instructional leadership also affects organizational commitment, but job satisfaction does not mediate the relationship, indicating that other factors may play a more significant role. In addition, work motivation negatively mediates the relationship between instructional leadership and organizational commitment. These findings provide important implications for educational policy and practice, emphasizing the importance of strategies that not only improve leadership effectiveness but also consider aspects of job satisfaction and motivation to strengthen the commitment of school principals in carrying out their duties.